Analysis of the Implementation of Village Fund Financial Accounting: Case Study in Semutan Village - Buyung Cahya Perdana (Journal of Economics, Management, Accounting, Business, Educational, Technology, and Social Science, 2024)
This research aims to analyze the implementation of Village Fund financial accounting in Semutan Village, with a focus on compliance with applicable regulations, effectiveness of recording, and transparency and accountability in Village Fund management. The research method used is a case study with a descriptive qualitative approach. Data was collected through interviews, observation, and analysis of village financial documents. The research results show that the implementation of Village Fund financial accounting in Semutan Village is by applicable regulations, but there are still several obstacles in terms of financial reporting and village officials' understanding of accounting concepts. Nevertheless, this village has demonstrated significant efforts to increase transparency and accountability through more open reporting to the community. The implication of this research is the importance of increasing human resource capacity at the village level through ongoing training and mentoring and developing a better accounting system. simple and easy to understand. In this way, it is hoped that Village Fund management will be more effective and accountable, which will ultimately support sustainable village development.